Geological map of Sulaimaniyah quadrangle, at scale of 1: 250 000 - Sissakian, Varoujan K.; Fouad, Saffa F. (Sulaimani Journal for Pure and Applied Sciences, 2016)
The geological map of Sulaimaniyah Quadrangle at scale of 1: 250 000 was first compiled by Iraq Geological Survey (GEOSURV) during 2007 depending; mainly on the available geological maps at scale of 1: 100 000, which were compiled from interpretation of aerial photographs, besides some other maps quoted from Kurdistan Series of geological maps and small parts mapped by GEOSURV during 1972 – 1974. The present geological map (2nd edition) also prepared by GEOSURV; however, includes a lot of updated data acquired from detailed geological mapping carried out during 2008 – 2009, and data acquired during systematic checking trips executed during 2007 – 2013 by the current authors. The updated geological map of Sulaimaniyah Quadrangle is attached by a geological report that describes the: Geomorphology, Structural Geology and Tectonics, Stratigraphy, Hydrogeology and Mineral Resources. Within all these subjects a lot of update data is presented, especially in Stratigraphy, and Structural Geology and Tectonics. The most updated parts of the Geological Map of Sulaimaniyah Quadrangle at scale of 1: 250 000 are those which are covered by Geological Maps of Sulaimaniyah, Qara Dagh and Halabja Quadrangles at scale of 1: 100 000, and more precisely the Sulaimaniyah Quadrangle, which is totally updated. The stratigraphic units are more accurately mapped and presented on the map, especially in the vicinity of Sulaimaniyah – Pera Magroon – Surdash – Haladin – Mawat – Azmir. The Quaternary sediments are more precisely presented on the map. Concerning the structural and tectonics, the structural elements; including anticlinal and synclinal axis and different types of faults are also more precisely presented on the current map too. However, still there are some parts that need updating within the current map, especially in areas where igneous and metamorphic rocks are exposed and in the extreme northeastern and northern parts of the map.
Keywords: Geological maQuaternarysedimentsCretaceousformations